2006
DOI: 10.1186/1742-4690-3-97
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir treatment augments anti-viral immunity against drug-resistant SIV challenge in chronically infected rhesus macaques

Abstract: These results support the concept that anti-viral immunity acts synergistically with ART to augment drug efficacy by suppressing replication of viral variants with reduced drug sensitivity. Treatment strategies that seek to combine immunotherapeutic intervention as an adjunct to antiretroviral drugs may therefore confer added benefit by controlling replication of HIV-1, and reducing the likelihood of treatment failure due to the emergence of drug-resistant virus, thereby preserving treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The absence of a rapid rebound in all three animals can theoretically be due to low replication fitness of the virus, to strong antiviral immune responses, or to a combination of both. Previous experiments demonstrated that SIV and RT-SHIV isolates having the K65R mutation in combination with compensatory mutations have high replication fitness and virulence, and generally do not revert back to wild-type sequence following tenofovir withdrawal [ 10 , 11 , 13 , 16 , 17 ]. Also in the current study, withdrawal of tenofovir treatment did not lead to a detectable reversion from K65R to wild-type virus.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a rapid rebound in all three animals can theoretically be due to low replication fitness of the virus, to strong antiviral immune responses, or to a combination of both. Previous experiments demonstrated that SIV and RT-SHIV isolates having the K65R mutation in combination with compensatory mutations have high replication fitness and virulence, and generally do not revert back to wild-type sequence following tenofovir withdrawal [ 10 , 11 , 13 , 16 , 17 ]. Also in the current study, withdrawal of tenofovir treatment did not lead to a detectable reversion from K65R to wild-type virus.…”
Section: Discussionmentioning
confidence: 99%
“…Although high levels of adherence have been reported in small-scale HIV programs in Sub-Saharan Africa [ 1 ], more challenges arise as these programs scale-up particularly in countries with a growing burden of HIV and tuberculosis (TB), and limited healthcare management facilities [ 2 ]. Rapid scale-up of antiretroviral therapy is accompanied by an increasing risk of ART failure resulting from HIV drug resistance and this is a major obstacle to successful ART in HIV-infected patients [ 3 ]. ART failure may result in progression to AIDS characterized by immunological and haematological complications and opportunistic infections [ 4 ] with increased risk of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…(2020) 75 , Metzner et al . (2006) 76 , and Stanford University HIV Drug resistance Database v.9.0, for Tenofovir, Emtricitabine, and Raltegravir.…”
Section: Methodsmentioning
confidence: 99%